If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4p-11p=4
We move all terms to the left:
4p-11p-(4)=0
We add all the numbers together, and all the variables
-7p-4=0
We move all terms containing p to the left, all other terms to the right
-7p=4
p=4/-7
p=-4/7
| -9x-2=24-9x | | 32x49=32x+36 | | 2(3x+1)=4(2x+3) | | 2.7=5.5-0.4x | | 37-6x=15+5x | | 0.03(54)+0.12x=0.06(x+54) | | -2x^2-3x+56=0 | | -87+5x=-4x+75 | | -3b+7=-2 | | -3x=-x-2x | | 4p-10=1p=3p-2p | | 15a^2-10a+3=0 | | 7x-179=73-2x | | 5(7–a)–3(a+4)–4=4(a–3)+7 | | 7x-8=-4x-8 | | x^2-33x=-16 | | 5x+2(6x-7)=139 | | 2c+3=c-4 | | 13x-61=9x+19 | | 3÷2y-y=4+1/2y | | 3x+2=1.5 | | 4^2b=1 | | 6x/9x=105 | | 4x+2=8+1x | | z-4+ -13=-10 | | 2x-2=57 | | 1/2x+3=2/3x-7 | | 6x-12+10x+20+80=90 | | 19x+1=15x+13 | | 19x+1=15x-13 | | X-3/7=5x | | 2x=1/4x-7 |